Perancangan House Of Cat Di Pekanbaru Dengan Pendekatan Modern Mies Van Der Rohe - Ruqayyah Nur Rachmah; Wahyu Hidayat; Gun Faisal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
House of cat is a forum for the cat lovers community in Pekanbaru as a rescue activity for stray cats, especially in the city of Pekanbaru. There are three stages in the Pekanbaru House of Cat in saving wild cats, that is rescue, rehab, and rehome. Rescue is the initial stage of saving cats from the street, rehab is a healing stage for a cat after being rescued from the street and rehome is a stage where a cat residing in the house of cat can be adopted and obtained a owner. The facilities provided to support the rescue of stray cats from the streets are in the form of a cat clinic for the first help in rescue, for the rehabilitation or healing stage of the room required in the form of a sterile room for the healing stage and other supporting rooms such as grooming for the cat's external body care. The design method used is the results of the field survey, documentation, and analysis of qualitative and quantitative data. The results of the design take shape from the general things used in rescue activities, namely the cage. The shape of the cage has a similarity to the principle of modern architectural design Mies van der Rohe, namely the presence of vertical and horizontal elements in its design. In addition to the three main functions, there are also supporting functions in the form of cat cafes, cat hotels and pet shops. Keywords: Pekanbaru city, cat, house of cat, modern Mies van der Rohe, cage